Incidence and demographic characteristics of Syrian Civil War-related amputations: A multi-center study - TATAR, YAŞAR (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2021)
Objectives: The aim of this study was to identify the causes, levels, and rates of amputations performed in civilians during the Syrian Civil War and to present epidemiological data of the amputees. Patients and methods: Between August 2017 and February 2019, a total of 363 amputations of 307 amputees (266 males, 41 females; mean age 29.9 +/- 13.3 years; range, 6 to 86 years) were retrospectively analyzed in four prosthesis and orthosis centers managed by an international non-governmental organization and serving to individuals who experienced amputation during Syrian Civil War. Level, etiology, number of amputations and distribution of the amputations by years were investigated. Results: Of the patients, 25.4% were under the age of 18 years. A total of 74% of all amputations were of the lower extremities. Transtibial and transfemoral amputations were the most common amputation levels. Of the amputees, 89.3% reported the cause of amputation as bombing. Conclusion: Civil amputations during the Syrian Civil War are different from those in other civil wars due to the high rate of bombing-induced amputations and also the high rate of victims under the age of 18 years. Our study results show a high ratio of both lower and upper extremity amputations in these civilians.
Keywords: Amputation; bombing; Syrian Civil War; LOWER-EXTREMITY AMPUTATION; COMBAT WOUNDS; LIMB LOSS; TRAUMA; MILITARY; INJURIES; OUTCOMES; EPIDEMIOLOGY; AFGHANISTAN; CASUALTIES